Inovasi Pembelajaran Digital Mata Kuliah Garap Pakeliran Era Merdeka Belajar-kampus Merdeka - Catur Nugroho; Sri Harti; Bagong Pujiono (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
The digital learning innovation of Garap Pakeliran II course is a grant program from the Indonesian Ministry of Education and Culture. This program is also an implementation of the Merdeka Belajar Kampus Merdeka (the Independent Study of Independent Campus). The innovation made is to transform learning materials into digital materials in the form of text and audio-visual. The Garap Pakeliran course is a compulsory practical course for students majoring in puppetry. The learning material is to direct students to be able to compose a good and qualified puppetry work. This activity can also be participated by students from outside ISI Surakarta as a form of application for the MBKM program. The digital material that was successfully compiled was then uploaded to the ISI Surakarta e-learning and YouTube page. Through these activities, students can learn independently and creatively as well as innovatively so that it is in accordance with what students want to do in relation to the preparation of puppetry works.